1992
DOI: 10.1073/pnas.89.7.3083
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling of the DNA topoisomerase and replication activities of an initiator protein.

Abstract: The replication initiator proteins encoded by the pT181 and related plasmids have sequence-specific DNA binding and topoisomerase activities. These proteins create a site-specific nick in one strand of the DNA at the origin of replication that serves as a primer for the initiation of replication. To define the regions of the pT181-encoded initiator protein, RepC, that are involved in its DNA binding, topoisomerase, and replication activities, we have carried out site-directed mutagenesis of the repC gene. Anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 24 publications
(22 reference statements)
1
36
0
Order By: Relevance
“…The binding of the RepC initiator protein to the pT181 origin was studied by gel mobility shift assays as described previously (5). The wild-type pT181 origin and the 18-bp subregion of IRII were cloned into the multiple cloning site of pUC19.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The binding of the RepC initiator protein to the pT181 origin was studied by gel mobility shift assays as described previously (5). The wild-type pT181 origin and the 18-bp subregion of IRII were cloned into the multiple cloning site of pUC19.…”
Section: Methodsmentioning
confidence: 99%
“…1). Subsequent studies showed that initiation of pT181 replication requires stable, sequence-specific binding of RepC to the origin (4,5). We performed gel mobility shift assays to test the requirement for RepC-origin interaction during the termination of replication.…”
Section: Relaxation Of Various Pt181 Origins By the Repc Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…A modular structure based on the presence of at least two domains involved in origin nicking and specific recognition of the dso sequence has been assumed to be a general feature of the initiator proteins of RCR plasmids (85)(86)(87)(88). This assumption could be valid for plasmids of the pT181 family, as the sequence-specific DNA binding and DNA relaxation activities of RepC, the initiator of pT181, are mutationally separable and lie on distant protein regions (86).…”
Section: The Replication Initiator Rep Proteinsmentioning
confidence: 99%
“…This assumption could be valid for plasmids of the pT181 family, as the sequence-specific DNA binding and DNA relaxation activities of RepC, the initiator of pT181, are mutationally separable and lie on distant protein regions (86). Taking advantage of this property, the identification of the role of individual monomers of pT181-RepC in RCR was addressed by generating heterodimers of the initiator containing a combination of wild-type, DNA binding, and nicking mutants (89).…”
Section: The Replication Initiator Rep Proteinsmentioning
confidence: 99%